Plastome-based backbone phylogeny of East Asian Phedimus (Subgenus Aizoon: Crassulaceae), with special emphasis on Korean endemics - Kim, Yongsung; Kim, Seon-Hee; Yang, JiYoung; Cho, Myong-Suk; Koldaeva, Marina; Ito, Takuro; Maki, Masayuki; Kim, Seung-Chul (Frontiers in Plant Science, 2023)
Although the monophyly of Phedimus has been strongly demonstrated, the species relationships among approximately 20 species of Phedimus have been difficult to determine because of the uniformity of their floral characteristics and extreme variation of their vegetative characters, often accompanied by high polyploid and aneuploid series and diverse habitats. In this study, we assembled 15 complete chloroplast genomes of Phedimus species from East Asia and generated a plastome-based backbone phylogeny of the subgenus Aizoon. As a proxy for nuclear phylogeny, we reconstructed the nuclear ribosomal DNA internal transcribed spacer (ITS) phylogeny independently. The 15 plastomes of subg. Aizoon were highly conserved in structure and organization; hence, the complete plastome phylogeny fully resolved the species relationships with strong support. We found that P. aizoon and P. kamtschaticus were polyphyletic and morphologically distinct or ambiguous species and they most likely evolved from the two species complex. The crown age of subg. Aizoon was estimated to be 27 Ma, suggesting its origin to be in the late Oligocene; however, the major lineages were diversified during the Miocene. The two Korean endemics, P. takesimensis and P. zokuriensis, were inferred to have originated recently during the Pleistocene, whereas the other endemic P. latiovalifolium originated in the late Miocene. Several mutation hotspots and seven positively selected chloroplast genes were identified in the subg. Aizoon.